Solution of mathematical model of volume solidification in castings using variation method - Kovač, Risto (Journal of Production Engineering, 1986)
The Galerkin method of variation is applied to solve mathematical model of volume solidification in infinite slab and to determine temperature field in casting. The solution of mathematical model is given in analytical-functional form, which is convinient for analysis of process. Relative fraction of solid state in mathematical model is defined by chinetical equation of solidification given by Kolmogorov.